The Effectiveness of the Student Activity Sheet (SAS) on Teaching-Learning and Creativity (TLC) Model to Increase Creativity Competence - Dwikoranto; Rahyu Setiani; Barokah Widuroyekti; Sri Tresnaningsih; Dwi Sambada; Titik Setyowati; Agus Rohman; Basuki Tri Harnoto (Indonesia Approach Education, 2020)
The purpose of this study explains the effectiveness of the student activity sheet model to enhance scientific creativity and student learning outcomes and student responses to the learning process. The research design used pre-experimental with one group pretest-posttest design. The study's subject was the student activity sheet (SAS) model and the implementation of primary teacher Education undergraduate students who programed a science introductory concept course during the 2019.1 registration at Open University. Data collected using test methods and questionnaires with product cognitive test instruments, cognitive process tests, scientific creativity tests and student questionnaire responses. Data analyzed by t-test and the proportions calculated. Normality test and homogeneity test are done before the t-test is applied. Increased creativity and student learning outcomes are calculated using normalized N-Gain. The results showed: 1) Improvement of students' scientific creativity after joining learning in the medium category. 2) Improving student learning outcomes after participating in learning in the good category. 3) Student responses to the learning process in the positive category. Based on the above, it can be concluded that the application of student activity sheet model used in learning activities to improve scientific creativity competency and student learning outcomes is effective.